Teaching Past Tense by Using Repetition and Substitution Drill to 5th Grade Students - Sumaira Chand, Rabia Tabassum, (JCTE, 2023)
The present study was aimed to investigate the effect of repetition and substitution drills method on the academic achievement of elementary school students in subject of English. The objectives of this study were (i) to find out the effectiveness of drill method on the construction of past tense ability, (ii) to find out the effect of substitution drill on the performance of the students, (iii) to investigate the effectiveness of repetition and substitution drills in improving the vocabulary of the students, (iv) To explore the effect of repetition and substitution drills method on the retention level of the students. To achieve the above objectives, the following null hypotheses were tested, (i) there is no significant effect of drill method on construction of past tense ability,